The global responsibility to prepare for intersecting climate and nuclear risks. (2nd November 2018) - Parthemore, Christine; Femia, Francesco; Werrell, Caitlin
ABSTRACT: The effects of climate change stand to heighten nuclear risks in various ways, including direct impacts on nuclear facilities, exacerbation of political and economic disruptions, and a diminishment of the strength of global institutions. Governments and international organizations have a responsibility to prepare for this collision of climate and nuclear threats, notably by using the unprecedented foresight that new technologies can provide.